Answer:
a)F=3 x 10⁻⁷ N
b)x=2.405 m
Explanation:
Given that
m₁=295 kg
m₂=595 kg
d= 4.1 m
a)
m₃=63 kg
r=d/2 = 2.05 m
The force between the mass m₁ and m₃
[tex]F_{13}=\dfrac{Gm_1m_3}{r^2}[/tex]
by putting the values
[tex]F_{13}=\dfrac{Gm_1m_3}{r^2}[/tex]
[tex]F_{13}=\dfrac{6.67\times 10^{-11}\times 295\times 63 }{2.05^2}[/tex]
F₁₃=2.94 x 10⁻⁷ N
The force between the mass m₂ and m₃
by putting the values
[tex]F_{23}=\dfrac{Gm_2m_3}{r^2}[/tex]
[tex]F_{23}=\dfrac{6.67\times 10^{-11}\times 595\times 63 }{2.05^2}[/tex]
F₂₃=5.94 x 10⁻⁷ N
The net force F
F= F₂₃- F₁₃
F=5.94 x 10⁻⁷ N-2.94 x 10⁻⁷ N
F=3 x 10⁻⁷ N
b)
Lest take at distance x from mass m₂ net force is zero.
[tex]F_{23}=\dfrac{Gm_2m_3}{x^2}[/tex]
[tex]F_{13}=\dfrac{Gm_1m_3}{(4.1-x)^2}[/tex]
Form above two equation
[tex]\dfrac{Gm_1m_3}{(4.1-x)^2}=\dfrac{Gm_2m_3}{x^2}[/tex]
[tex]\dfrac{m_1}{(4.1-x)^2}=\dfrac{m_2}{x^2}[/tex]
[tex]\dfrac{295}{(4.1-x)^2}=\dfrac{595}{x^2}[/tex]
x²=2.01(4.1-x)²
x=1.42 (4.1-x)
x=5.82 - 1.42x
x=2.405 m